Physico‑chemical analysis of the oleoresin and genetic variability of copaiba in the Tapajós National Forest, Brazil - Silva, Ederly Santos; Mathias, Caroline de Souza; Lima, Milena Campelo Freitas de; Veiga Junior, Valdir Florêncio da; Rodrigues, Doriane Picanço; Clement, Charles Roland (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to characterize the oleoresin of copaiba (Copaifera reticulata) and to estimate genetic variability of the species in the Tapajós National Forest, PA, Brazil, using microsatellite markers. Sampling was performed in two areas, 5 km apart, in 136 trees. Genetic diversity was evaluated with six microsatellite markers derived from C. langsdorffii, and the oleoresin obtained from 30 trees (15 from each area) was physically and chemically characterized. Oleoresin from C. reticulate has a liquid, thin aspect, with a weak odor and yellowish‑gilded color (73.3% of the plants), highly variable viscosity (18 to 187 Pa-s), and mean density of 0,975±0,049 g cm-3. Its acidity index varied from 9.62 to 10.17 mg g-1 of KOH and the saponification index from 100.63 to 109.84 mg g-1. The molecular analysis identified 78 alleles, with an average of 13 per locus. The expected heterozygosity varied from 0.59 to 0.85 (mean of 0.75) and the inbreeding level, from 0.375 to 0.419. The genetic differentiation between populations in the different sampling areas was low (FST = 0.030), but the variability was higher between the genetic groups detected by Structure software (FST = 0.070). This higher variability indicates that the genetic diversity of copaiba is not threatened in the mid‑term.